Building pro-environmental behavior among school community of Adiwiyata green school - Nurwidodo, Nurwidodo; Al Muhdhar, Mimien Henie Irawati; Rohman, Fatchur; Iriani, Dwi; Herlina, Herlina; Fausan, Muhammad Mifta (Jurnal Pendidikan Biologi Indonesia, 2019)
Efforts to build pro-environment behavior have been strengthened by the Ministry of Environment and Forestry through Adiwiyata green school program. This current study aimed at describing the patterns of building pro-environmental behavior among school community of Adiwiyata green school in Malang City. This study was conducted by means of descriptive design. The data were collected using in-depth interview, directed observation, and documentation as well as triangulation. The data were analyzed descriptively by means of content analysis. Hereafter, this study has shown that SMAN 7 Malang was and is running a program of pro-environmental behavior building offered to all school community, to enhance the knowledge, to fossilize the behavior, and to implement pro-environmental behavior, with the concrete support from the school management and teachers. The program was run sustainably and supported by education authorities along with pro-environmental communities. To sum up, the patterns of building pro-environmental behavior involved all the school community, to cover such aspects as knowledge enhancement, behavior fossilizing, and pro-environmental behavior reinforcement through a sustainable collaboration with pro-environmental communities. Therefore, it is suggested that Adiwiyata green school keep intensifying its commitment and be consistent in building sustainable pro-environmental behavior to amplify a long-term memory of its school community.